Simvastatin targets the cholesterol–bile acid axis to improve ALL survival by remodeling the metabolic microenvironment - Junyu Wang; Bo Jiao; Tuantuan Gui; Xuan Liu; Shan-Shan Guo; Cheng Wang; Weiyang Liu; Li-Jun Peng; Jiayi Ren; Ming Zhang; Yun Tan; Duohui Jing; et al. (Blood, 2025)
Abstract Acute lymphoblastic leukemia (ALL) is a highly heterogeneous hematologic malignancy, with pathogenesis closely linked to metabolic reprogramming. Emerging evidence has implicated dysregulated lipid metabolism as a key driver of leukemic progression and therapeutic resistance. In our prior work [Guo et al. Journal of Translational Medicine (2025). doi:10.1186/s12967-025-06423-4], we demonstrated that decreased mitochondrial activity induces multidrug resistance in adult T-ALL through lipid-mediated activation of ABCB1, which was significantly associated with poorpatient overall survival. In another study [Wang et al. PNAS (2025). doi:10.1073/pnas.2423169122], we identified reduced serum cholesterol levels and aberrant activation of bile acid biosynthesis in ALL patients. That study established taurocholic acid (T-CA) as an independent prognostic biomarker and showed that exogenous T-CA in a high-risk genotype of MEF2D::HNRNPUL1 and NRASG12D (MH/N) B-ALL murine models promotes hepatic leukemic infiltration, whereas the simvastatin-chemotherapy combination improves survival potentially by regulating the liver microenvironment, which influences BA levels as well as T cell and myeloid cell-associated immune regulation. Despite these findings, the mechanistic links between metabolic reprogramming and immune dysregulation in ALL remain elucidated. To address this, we first validated the prognostic value of T-CA, demonstrating that both circulating and intracellular T-CA levels independently predict adverse outcomes. We then tested the hypothesis that simvastatin enhances chemotherapy efficacy by reprogramming the hepatic immunometabolic niche. Clinical analyses of 64 B-ALL patients with high peripheral blast burden (defined by peripheral blast counts >50% via flow cytometry) revealed significant correlations between bile acid profiles and immune parameters. Specifically, T-CA and most of the other bile acids were positively correlated with CD19⁺ blast percentage, CD4⁺ T-cell infiltration, and serum IL-6 levels, while negatively correlated with NK cell populations and IL-2R expression. Transcriptomic profiling of MH/N B-ALL murine models revealed substantial molecular heterogeneity between liver-infiltrating and bone marrow-resident leukemic cells. Notably, the simvastatin-chemotherapy combination group—associated with superior survival—exhibited a unique hepatic gene expression signature distinct from those observed in the control groups. This transcriptional divergence strongly suggests that microenvironmental remodeling underlies simvastatin's synergisticeffect. Gene set enrichment analysis (GSEA) further indicated that liver-infiltrating leukemic cells in the simvastatin combined treatment group were significantly enriched for pathways related to metabolic reprogramming, immune modulation, and signal transduction. These features were not observed in their bone marrow-resident counterparts. Collectively, our findings suggest T-CA as a clinically promising biomarker and demonstrate that simvastatin's synergisticefficacy is mediated through metabolic-immune niche reprogramming, providing a rational basis for microenvironment-targeted therapies.